2017
DOI: 10.1039/c7ra11585g
|View full text |Cite
|
Sign up to set email alerts
|

Degradation of battery separators under charge–discharge cycles

Abstract: Researchers have reported on the electrochemical aging of lithium-ion batteries. The mechanisms of battery capacity loss, such as consumption of electrolytes and fading of electrodes, commonly seen as fracture of coatings, have been studied intensively. The widely used polymeric separators sandwiched between cathode and anode, which do not directly contribute to the electrochemical properties of the cell, are usually taken as chemically, thermally and structurally stable materials. In this paper, the degradati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 68 publications
(52 citation statements)
references
References 19 publications
3
49
0
Order By: Relevance
“…This is consistent with previous studies of dry processed polymeric separators by Zhang et al 25,26 For the axial compression loading case, no significant difference was observed between location of first peak and onset of short circuit between dry and wet cells. In the case of the hemispherical punch indentation, no difference was observed in the fracture patterns between wet and dry cells, both having cracks in the direction parallel to the MD.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This is consistent with previous studies of dry processed polymeric separators by Zhang et al 25,26 For the axial compression loading case, no significant difference was observed between location of first peak and onset of short circuit between dry and wet cells. In the case of the hemispherical punch indentation, no difference was observed in the fracture patterns between wet and dry cells, both having cracks in the direction parallel to the MD.…”
Section: Discussionsupporting
confidence: 93%
“…A recent review on the modeling of lithium-ion cells revealed 1 that previous studies have focused mostly on two common form factors, pouch 2-7 and cylindrical [7][8][9][10][11][12][13][14][15][16][17][18][19] cells and their components. [20][21][22][23][24][25][26] A third type of batteries commonly used in various applications such as electric vehicles is the prismatic cell. The main difference between prismatic and cylindrical cells is the arrangement of electrode-separator layers.…”
Section: Introductionmentioning
confidence: 99%
“…36 By leveraging known trends in how a structure of a given topology shrinks under thermal stress, 37 deforms in response to compressive or tensile stresses, 38,39 or maintains connectivity despite closing of branches or nodes, 36 it will be possible to predict a separator's response to many of the dynamic processes experienced during cell manufacturing and operation. 40 Connectivity density can be calculated via a Minkowski functional and is important when describing homogenisation of ion concentration gradients across microstructures. Similarly, other morphological and topological parameters are helpful when assessing surface interactions and effects.…”
Section: Discussionmentioning
confidence: 99%
“…Under the stress of external shock, the microporous polyolefin separator can easily deform, accompanied with the change of inside porous network, including the pore closure, leading to the inhomogeneous Li + ion flux in the battery . The nonuniform Li + ion flux can then create high local current density to trigger lithium dendrite growth on the electrode, resulting in short circuit and even explosion of lithium batteries …”
mentioning
confidence: 99%
“…[11] The nonuniform Li + ion flux can then create high local current density to trigger lithium dendrite growth on the electrode, resulting in short circuit and even explosion of lithium batteries. [12][13][14][15] Currently, ceramic nanoparticle coat ings are widely used to protect micro porous polyolefin separators because of their good electrolyte wettability and high thermal stability. [16,17] However, these ceramic nanoparticle coatings cannot provide enough protec tion for the microporous polyolefin separators against external impacts because of the limited mechanical energy dissipation capabilities.…”
mentioning
confidence: 99%